Perbandingan Ekonomi Islam dan Ekonomi Kapitalis - Muslims, Moch Bukhori (Faculty of Shariah and Law, 2012)
This greatness of the capitalist economic theory has been questioned by many prominent economists. Due to the economic crisis occured througout history, it is necessary to bring out an alternative economic theory. Economic theory aspired is an economic system that is able to create justice and the welfare accompanied with blessing the world and the hereafter. Therefore, Islamic economic theory can be considered as a way out to solve the contemporary economic probles. This article compare the system of Islamic economic and the capitalist economic taking into account the philosophy, investment, distribution, theory of macro and micro aspects.DOI: 10.15408/aiq.v4i2.2103